2013
DOI: 10.1192/apt.bp.112.010363
|View full text |Cite
|
Sign up to set email alerts
|

Boredom among psychiatric in-patients: does it matter?

Abstract: SummaryMany psychiatric in-patients report boredom. Such complaints may appear trivial, but this literature review by a clinical librarian suggests that boredom is more complex than may initially appear and relates to wider areas of importance for in-patient psychiatric teams. Boredom may relate to the internal experience of meaning, which itself encompasses meaningful relationships and roles and a sense of control. Although meaningful therapeutic activities are vital, mental health professionals should focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Situation-dependent boredom is externally driven, primarily due to a monotonous environment. In contrast, situation-independent boredom arises from internal factors (Todman 2003; Steele 2013). Proponents of situation-independent boredom believe that boredom results from an inability to use coping mechanisms such as fantasy and anticipation to escape from monotony (Todman 2003).…”
Section: Theories Of Boredommentioning
confidence: 99%
See 1 more Smart Citation
“…Situation-dependent boredom is externally driven, primarily due to a monotonous environment. In contrast, situation-independent boredom arises from internal factors (Todman 2003; Steele 2013). Proponents of situation-independent boredom believe that boredom results from an inability to use coping mechanisms such as fantasy and anticipation to escape from monotony (Todman 2003).…”
Section: Theories Of Boredommentioning
confidence: 99%
“…As mentioned above, those who espouse the theory of situation-dependent boredom argue that boredom is primarily due to a monotonous environment. They suggest that individual differences reflect a differing level of vulnerability to the absence of environmental stimuli, with individuals more prone to boredom using particular (usually maladaptive) behaviours or traits (Steele 2013). An inability to maintain attention on the non-social environment, and a lack of cognitive stimulation in one’s life, could be regarded as a ‘maladapative’ trait (although a lack of cognitive stimulation in one’s life is not necessarily something for which we can blame the individual).…”
Section: Boredom and Cognition In Elderly Peoplementioning
confidence: 99%
“…14 Figure 3 shows that, although NICE guidelines and randomised controlled trials (RCTs) were available to illuminate boredom among psychiatric in-patients, other research designs which are conventionally considered to be ‘lower’ in the evidence hierarchy were also synthesised by the CL.…”
Section: Resultsmentioning
confidence: 99%
“…14 A consultant clinical psychologist likewise perceived the CL role in the context of clinical governance and as integral to supporting research and development and issues core to the business of mental health trusts, commenting:…”
Section: Resultsmentioning
confidence: 99%
“…This argument suggests that psychiatric patients find smoking pleasurable and stress‐reducing and that removing this source of comfort during the stressful period of admission is cruel and unnecessary (Lawn & Condon, ). It is well documented that patients often experience boredom during psychiatric admissions (Farnworth, Nikitin, & Fossey, ; Newell, Harries, & Ayers, ; Steele, Henderson, Lennon, & Swinden, ) and that boredom is related to negative emotions that psychiatric patients frequently experience including apathy, anhedonia and depression (Goldberg, Eastwood, Laguardia, & Danckert, ). It has also been shown that in the absence of smoke‐free policies, psychiatric patients may start smoking while admitted to reduce boredom and patients who smoked prior to admission smoke more postadmission (Ker & Owens, ).…”
Section: Critical Examination Of Arguments Against Smoke‐free Mental mentioning
confidence: 99%